Letter - Samuel, G.
035-0136-001 South Wales Miners' Federation. Area No 5 Tower Lodge. 32 Cemetery Rd Trecynon Aberdare 4/9/42 The Secretary Trades Union Congress London. Sirs I am instructed by my committee to forward the following resolution for your sympathetic consideration. "(a) That the National Executive should approach the Foreign Office to demand that the British Government in collaboration with the American Government negotiate the realease of members of the International Brigade still confined to the concentration camps in France and North Africa. b/ That the National Executive should have the matter of their release raised by M.P.s in Parliament. c/ That the National Executive should themselves support the efforts of the International Brigade Association for the relief and release of International Brigaders. On behalf of the Tower Lodge Committee Yours truly G.J. Samuel Sec EAB 292/946/35/136